Intrinsic Motivation, Resilience, And Teamwork On Employee Performance Through Co-Worker Support - Indar Widana; Sugeng Haryanto; Mohammad Choldum Sina Setyadi (Business Management Research, 2026)
Employee performance in public sector organizations is often shaped not only by individual capability but also by social and collaborative workplace dynamics. However, previous studies have reported inconsistent findings regarding the effects of intrinsic motivation, resilience, and teamwork on employee performance, particularly within field-based public service settings. This study aims to examine the influence of intrinsic motivation, resilience, and teamwork on employee performance, with co-worker support serving as a mediating variable among employees of the Green Open Space Division at the Malang City Environmental Service. This study employed a quantitative explanatory approach using purposive sampling. Data were collected from 126 employees and analyzed using Structural Equation Modeling (SEM-PLS). The findings reveal that resilience and teamwork positively and significantly affect employee performance, while intrinsic motivation has no direct effect. Co-worker support significantly enhances employee performance and partially mediates the relationships between resilience, teamwork, and employee performance. In contrast, the mediating role of co-worker support in the relationship between intrinsic motivation and employee performance was not supported. The study contributes to public sector human resource management literature by emphasizing the importance of social work factors, particularly teamwork and co-worker support, in strengthening employee performance within operational public service environments.